Percepção de estudantes sobre a física no ensino médio: o eletromagnetismo em estudo - PASSOS, Luiz Vinicius Silva dos (2024)
This research analyzes the perception of high school students and teachers about the teaching of Physics in the city of Abaetetuba-PA, focusing on the Consensual Qualitative Research (CQR) methodology, a constructivist approach with an ontological perspective that reflects the epistemological matrix characterized by the non-separation between the subject and the object of knowledge. The role of the scientist is to seek experiential commonalities among the participants in the investigation (HILL et al., 2005). Semi-structured questionnaires were applied to two Physics teachers and 64 third-year high school students, considering a general sample and gender variables. The analysis, based on Hill et al. (1997) categories, covered the perception of Physics teaching, its relation to daily life, the use of didactic materials, and laboratories. The results show that students relate Physics to everyday life and find it difficult to understand the content, mainly due to the lack of practical demonstrations or because they do not understand the teachers’ explanations very well. Both male and female high school students participating in the research suggest that Physics is better explained with experimental resources, laboratories, and projects. The teachers recognize that the students’ difficulties lie with the theory and wish to use more dynamic methodologies, but the lack of resources limits access to basic materials, compromising the teaching and learning process.